Developing enterprise-wide business process management capability : a teaching case from the financial sector - Bandara, Wasana; Abbott, Charon; Mathiesen, Paul; Meyers, Lara; Nagra, Mindy (London : Palgrave MacMillan UK, 2018)
Continuously managing business processes is globally a high organisational priority. The necessity for organisation-wide process management approaches (as opposed to ad hoc initiatives) is widely recognised. Yet, the required skills and capabilities for such enterprise-wide BPM is a well-known gap, with little resources to date to address this. This teaching case is based on the Bank of Queensland (BOQ—one of the oldest financial institutions in Australia). The narrative provides an overview of a range of Enterprise level business process management (hereafter referred to as ‘E-BPM') activities that have taken place to date at BOQ to build its E-BPM capability.
Originally Published InBandara, W., Abbott, C., Mathiesen, P., Meyers, L., & Nagra, M. (2018). Developing enterprise-wide business process management capability: A teaching case from the financial sector. Journal of Information Technology Teaching Cases, 8, 192–208.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Workflow -- Management; Industrial management